Medical Economics: Legalize Organ Markets - Callais, Justin; Block, Walter E. (Bina Nusantara University, 2017)
The article argued to the contrary that at least insofar as organ transplants were concerned, this general assumption lied 180 degrees away from the truth. The first reaction of most concerned people, at the prospect of buying and selling human body parts, was one of revulsion. And, yet, this was the tried and true means that used for supplying more pedestrian goods and services. The article was the economic principles responsible for adequately making available to us such as items such as apples, shoes, and gardening services were the best ones in this case as well. The method was to argue that the institutions responsible for most goods and services in the economy that the last best hope for solving the problems that faced transplants of human body parts. The researchers consulted google scholar and mises.org and generated in this manner and cited almost a dozen publications which discussed the relevant subject matter and commented on several of them. It finds that Pro-organ sellers have a long way to go, but with determination and logic, one day the world will find a place for organs in the free-markets. And, then, many lives will be saved.